Enhanced optical nonlinearity and ultrafast carrier dynamics of TiO2/CuO nanocomposites. (15th May 2022) - Dong, Li; Chu, Hongwei; Li, Ying; Zhao, Shengzhi; Li, Dechun
Abstract: Transition metal oxides (TMOs) are drawing multitudinous interest due to their strong thermochemical stability. In the present work, we proposed a facile strategy to fabricate TiO2 /CuO nanocomposites. By using the conventional open- and closed-aperture Z-scan technology, the eminent nonlinear optical (NLO) properties of the as-prepared TiO2 /CuO nanocomposites were demonstrated. In order to deeply investigate the NLO enhancement mechanism, we established a theoretical model to study the photogenerated carriers transfer dynamics at the interface with rate equations and the fouth-order Runge-Kutta algorithm. The simulation results indicated that under pumping irradiation, the carriers transferring from CuO to TiO2 promoted the nonlinear optical absorption of CuO nanosheets and increased the modulation depth. Experimentally, the transient absorption spectroscopy and broadband time-resolved pump-probe measurements were presented to study the role of the carrier dynamics in the broadband near-infrared region. To further confirm the enhanced NLO response in TiO2 /CuO nanocomposites, a highly stable dissipative soliton mode-locked Yb-doped fiber laser with TiO2 /CuO saturable absorber was constructed at 1 μm for the first time. Our work manifested the key effects of the interface in TiO2 /CuO nanocomposites to boost the NLO features which can be applied in ultrafast photonics applications.